2007
DOI: 10.1111/j.1471-6712.2007.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Swedish version of the Resilience Scale

Abstract: The aim of this study was to investigate resilience in relation to age and gender, and to elucidate the underlying structure of the Swedish version of the Resilience Scale (RS). The RS, originally created by Wagnild and Young is a 25 items scale of Lickert type with possible scores ranges from 25 to 175, the higher the score, the stronger resilience. A standardized procedure was used for translation. The analysis was based on 1719 participants, 1248 women and 471 men, from eight different samples, aged from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
90
10
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 35 publications
18
90
10
21
Order By: Relevance
“…Male students are more resilient as compared to female students in Pakistan for reasons not measured here. These results are contradictory to Uzma (2007) who found that in Pakistan, female students are more resilient than their male counterparts, which may be that the resilience is related to age (Lundman, et al, 2007). Uzma (2007) conducted her study on post-graduate university students, but in the present study, the students are secondary school level.…”
Section: Discussioncontrasting
confidence: 83%
“…Male students are more resilient as compared to female students in Pakistan for reasons not measured here. These results are contradictory to Uzma (2007) who found that in Pakistan, female students are more resilient than their male counterparts, which may be that the resilience is related to age (Lundman, et al, 2007). Uzma (2007) conducted her study on post-graduate university students, but in the present study, the students are secondary school level.…”
Section: Discussioncontrasting
confidence: 83%
“…However, resilience has more recently been shown to increase with age (Lundman, Strandberg, Eisemann, Gustafson, & Brulin, 2007). The few reported findings on the relation between RS score and gender have not been consistent.…”
mentioning
confidence: 95%
“…Por outro lado, contrariam as conclusões do mesmo autor com relação à variável idade, uma vez que, a este respeito, nenhum dos estudos mostrou diferenças significativas. Entretanto, autores como Lundman et al (2007) encontraram relações positivas entre a idade e resiliência, justificando estes dados a partir da análise da resiliência como um processo que ocorre durante toda a vida das pessoas. Este aspecto é também teoricamente defendido por outros pesquisadores (ver: Galli & Vealey, 2008;Luthar et al, 2000;Rutter, 2006).…”
Section: Resultsunclassified
“…Isto não teria ocorrido em outras pesquisas, onde a variabilidade das idades dos sujeitos era menor. Lundman et al (2007) argumentam ainda que a resiliência deveria ser considerada como um processo, o qual, não sendo estático, poderia mudar ao longo da vida, o que explicaria também os seus resultados.…”
Section: Introductionunclassified